Risk factors for local recurrence of early bilateral vocal cord carcinoma treated with transoral CO2 laser microsurgery. (1st September 2021) - Tan, Chen; Fang, Jugao; Wang, Ru; Zhong, Qi; Hou, Lizhen; Ma, Hongzhi; Feng, Ling; He, Shizhi; Lian, Meng; Yang, Yifan
Abstract: Background: The incidence of local recurrence after transoral CO2 laser microsurgery for T1b–T2 glottic carcinoma is relatively low. Multiple risk factors have been described for the development of local recurrence after treatment. However, to date, there is no analysis or systematic review investigating the relationships between clinical and histopathological factors and the appearance of local recurrence after transoral CO2 laser microsurgery in T1b–T2 glottic carcinoma patients. Aims/objective: To investigate risk factors for local recurrence after CO2 laser surgery in T1b–T2 glottic carcinoma involving bilateral vocal cords. Material and methods: We retrospectively studied patients undergoing CO2 laser surgery for T1b–T2 glottic carcinoma involving bilateral vocal cords. Multiple follow-up laryngoscopies and computed tomographies were performed. Main outcome measures: survival rate, local recurrence rate, and independent risk factors for recurrence. Results: All 85 patients (83 male; age, 63.33 ± 10.59 years; 36 T1b and 49 T2 lesions; 28 cases with and 57 without anterior commissure (AC) involvement) survived; 15 exhibited postoperative local recurrence. Recurrence rates differed between the following groups: patients without (6/57) versus patients with AC involvement (9/28) ( p  = .007); patients with negative (11/77) versus positive resection margins (4/8) ( p  = .014); p53-negative (5/51) versus p53-positive patients (10/34) ( p  = .0132). AC involvement, positive resection margins, and p53 expression were independent risk factors for recurrence. Conclusions: Patients with stage T1b and T2 glottic carcinoma with AC involvement, positive resection margins, and p53 expression should be followed up at shorter intervals. Significance: This article provided valid clinical data for risk factors for local recurrence after CO2 laser surgery for T1b–T2 glottic carcinoma involving bilateral vocal cords.